A Comparative Plume Study of DRO, GRO, Benzene, and MTBE: Implications for Risk Management. Issue 3 (5th April 2021) - O'Reilly, Kirk; Lahvis, Matthew A.; DeVaull, George E.; Deines, Andrew M.
Abstract: Groundwater remediation and no‐further action decision making at petroleum underground storage tank (UST) sites has largely been based on an understanding of plume length, plume stability, and attenuation rates for key hydrocarbon constituents. Regulatory guidance to support and guide such decisions is based in part on plume studies involving individual hydrocarbon constituents, namely benzene and methyl tert‐butyl ether (MTBE). Questions remain regarding whether current guidance is applicable to chemical mixtures such as gasoline range organics (GRO), diesel range organics (DRO), and oxygen containing organic compounds (OCOCs) resulting from hydrocarbon biodegradation. To help address this concern, data from California's GeoTracker database were used to estimate maximum plume lengths, plume stability, and attenuation rates of DRO (which can be used as an analytical surrogate for OCOCs) and GRO relative to benzene and MTBE. The distributions of maximum plume lengths were similar for the four constituents with medians ranging from 27 to 32 m. The fraction of monitoring wells with a decreasing concentration trend ranged from 19% for DRO to 40% for MTBE, while fewer than 7% of the wells had an increasing concentration trend for any of the constituents. Median attenuation rates ranged from 0.10% day −1 for DRO to 0.17% day −1 for MTBE. The results suggest attenuation based risk management is appropriate for DRO and GRO plumes at most petroleum UST sites. Abstract : Article impact statement : This paper compares the attenuation behavior of DRO to other gasoline constituents and considers the risk management implications.